Cross-talk with β2-adrenoceptors enhances ligand affinity properties from endothelial alpha1D-adrenoceptors that mediates carotid relaxation - Pernomian, Larissa; Gomes, Mayara Santos; Restini, Carolina Baraldi Araujo; Pupo, André Sampaio [UNESP]; De Oliveira, Ana Maria (Oxford University Press (OUP), 2013)
Objectives Our main objectives were to investigate the affinity properties of endothelial and muscular α1D-adrenoceptors and to characterize the cross-talk between endothelial α1D- adrenoceptors and β2-adrenoceptors in rat carotid. Methods Relaxation and contraction concentration-response curves for phenylephrine (α1-adrenergic agonist) were obtained in carotid rings in absence or presence of increasing concentrations of BMY7378 (α 1D-adrenergic antagonist), combined or not with increasing concentration of ICI-118,551 (β2-adrenergic antagonist). Schild analysis was used to estimate the affinity constant from pA2 values of BMY7378. Key Findings BMY7378 produced an unsurmountable antagonism on phenylephrine-induced relaxation but a surmountable antagonism on phenylephrine-induced contraction. BMY7378 potency was higher in inhibiting the relaxation than the contraction induced by phenylephrine because the rightward shifts induced by BMY7378 were greater in the relaxation. The apparent pA 2 value for BMY7378 in phenylephrine-induced relaxation was greater than in contraction. When combined with ICI-118,551, BMY7378 yielded a surmountable antagonism on phenylephrine-induced relaxation and presented a pA2 value similar to that obtained in phenylephrine-induced contraction. Conclusions Endothelial α1D-adrenoceptors, which mediates rat carotid relaxation, present high ligand affinity because of the cross-talk with β2-adrenoceptors, which explains the higher potency of phenylephrine in inducing relaxation than contraction and the atypical unsurmountable antagonism produced by BMY7378 on phenylephrine-induced relaxation. © 2013 Royal Pharmaceutical Society.
Keywords: molecular and clinical pharmacology; molecular and receptor pharmacology; other topics; tissue and cellular pharmacology; 3 isopropylamino 1 (7 methyl 4 indanyloxy) 2 butanol; 8 [2 [4 (2 methoxyphenyl) 1 piperazinyl]ethyl] 8 azaspiro[4.5]decane 7,9 dione; alpha 1D adrenergic receptor; beta 2 adrenergic receptor; cyclic AMP; nitric oxide; phenylephrine; potassium channel; animal cell; animal tissue; artery constriction; binding affinity; carotid artery; controlled study; coronary artery dilatation; endothelium cell; gap junction; male; muscle cell; nonhuman; rat; signal transduction